Visualizing walkability: exploring residents' preferences for complete street design and urban trails using immersive 360° videos - Gillespie, Chloe S. (Kansas State University, 2023)
Complete streets and pedestrian-oriented design have been a pressing issue in cities over the past 20 years. While the safety benefits of having complete streets have been explored widely (Burlacu & Tărîţă-cîmpeanu 2016; Litman 2015; Kwon et al. 2022), less attention has been paid to the role comfort level and aesthetic quality has in walkability. This study aims to address this issue by examining people’s perceptions towards pedestrian-oriented street designs along an urban streetside interpretive trail. More specifically, this study investigates how sidewalk widths, plantings, and bike lanes influence people’s comfort level, perceived safety, and aesthetic preference towards a space. Using a virtual reality experience with 360° video, data was collected from a population of 53 participants in a study area in eastern Kansas City, Missouri. In this study, participants viewed three focus areas each with three different interventions of added pedestrian-oriented complete street elements including sidewalk width, planting, and bike lane, and ranked their levels of comfort, safety, and attractiveness for the space on a five-point rating scale. The results indicate the extent to which complete street elements contribute to creating more walkable spaces from users’ perspective. The statistical analysis results revealed that increased sidewalk width and flowered plantings had the greatest influence in increasing feelings of walkability. Building upon these findings planning and design interventions were proposed for each focus area type. The broader outcome of this study relates to its implications in highlighting the use of VR and 360° videos in understanding people’s preferences for urban streetside interpretive trail design, and how 360° technology can be used as a research and design tool.
Keywords: Walkability; 360° video; Urban trails; Comfort, safety, and attractiveness perceptions; Complete street